Rasionalitas Investor Terhadap Pemilihan Saham Dan Penentuan Portofolio Optimal Dengan Model Indeks Tunggal Di BEJ - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
Rational investors will invest their funds in efficient stock which provides high expected return with minimum risk. Security analysts employ such methods as a single index model to evaluate the efficient portfolio that lived at the efficient frontier. This research covers securities on ILQ-45 which have the greatest market capitalization, and the most liquid in terms of trading frequency. Since the purpose of diversification is to enhance portfolio return and to minimize risk, the main purpose of this research is to ascertain the optimal portfolio. Empirical evidence indicates that three of twenty five stocks make up the best portfolio candidates: Lippo Land Development (LPLD), Astra International Inc. (ASH), and Gudang Garam (GGRM), with excess returns to beta (ERB) of 6.2621, 1.7987 and 0.6866 respectively. The high cut-off rate (C*) of 0.5629, indicates that these three stocks are the best portfolio candidates. The optimum portfolio comprises 51.32% LPLD, 47.55% ASH and 1.13% GGRM stock, with a return portfolio of 2.73%, beta portfolio of 0.4188 and portfolio risk of 2.7138. In conclusion, rational investors will invest their funds in optimum portfolio. Empirical evidence indicates a significant difference in the mean of twenty-two stocks, and reveals three stocks as optimum portfolio candidates at 303.9313. The test of variance-equal is significant at 0.031 and F= 4.899.